Through a Glass Darkly: Contested Notions of Baptist Identity - Byrd, James P (Religion and American Culture Ser, 2012)
Normal0falsefalsefalseMicrosoftInternetExplorer4Through a Glass Darkly is a collection of essays by scholars who argue that Baptists are frequently misrepresented, by outsiders as well as insiders, as members of an unchanging monolithic sect. In contemporary discussions of religious denominations, it is often fashionable and easy to make bold claims regarding the history, beliefs, and practices of certain groups. Select versions of Baptist history have been used to vindicate incomplete or inaccurate assertions, attitudes, and features of Baptist life and thought. Historical figures quickly become saints, and overarching value systems can minimize the unsavory realities that would contribute to a truer interpretation of Baptist life. The essays in this volume use the term Baptist in the broadest sense to refer to those Christians who identify themselves as Baptists and who baptize by immersion as a non-sacramental church rite. Over the past four hundred years, Baptists have grown from a persecuted minority to a significant portion of America's religious population. They have produced their fair share of controversies and colorful characters that have, in turn, contributed to a multifaceted history. But what does it mean to be a "real Baptist"? Some look to historical figures as heroic exemplars of Baptist core values. Others consider cultural, social, or political issues to be guideposts for Baptist identity. Through a Glass Darkly dives deeper into history for answers, revealing a more complete version of the expansive and nuanced history of one of America's most influential religious groups. Normal0falsefalsefalseMicrosoftInternetExplorer4Contributors:James P. Byrd / John G. Crowley / Edward R. Crowther / Christopher H. Evans / Elizabeth H. Flowers / Curtis W. Freeman / Barry G. Hankins / Paul Harvey / Bill J. Leonard / James A. Patterson /